Pandangan Hukum Islam Terhadap Komunikasi Interpersonal Pasangan Suami Dan Istri Dalam Menentukan Jumlah Anak - Adawiyah, Robiatin; Zaelani, Abdul Qodir; Nurnazli, Nurnazli; Pujianti, Etika (JUSTICIA SAINS - Jurnal Ilmu Hukum, 2025)
This study aims to examine how interpersonal communication between husband and wife plays a role in decision-making regarding the number of children, viewed from the perspective of Mubādalah. This study uses a qualitative descriptive method with a library research approach, which examines various literature such as books, journal articles, and other relevant references. The results of the study indicate that effective interpersonal communication is characterized by openness, empathy, the ability to listen actively, honesty in expressing opinions, and emotional support has a major influence on the negotiation process and joint decision-making regarding the number of children. The Mubādalah perspective provides a theological and ethical framework in building equal partnerships, as well as correcting hierarchical relationship patterns that often place women's voices in a less prioritized position. By using the principle of Mubādalah, the decision on the number of children is not only understood as a technical issue, but also as a spiritual and moral discourse, where husband and wife have equal responsibility and authority in conveying their hopes, concerns, and limitations. This mutually respectful communication is the foundation for the formation of a harmonious and democratic family.]